RETRACTED: A Psychosocial Exploration of Body Dissatisfaction: A Narrative Review With a Focus on India During COVID-19 - Ahuja, Kanika K.; Banerjee, Debanjan (Frontiers in Global Women's Health, 2021)
COVID-19 has been an unprecedented global crisis. Besides the public health impact, the pandemic necessitated measures like quarantine, travel restrictions and lockdown, that has had a huge effect on digital screen time, dietary habits, lifestyle measures and exposure to food-related advertising. At the same time, reduced physical activity, increased consumption of social media, and fitness tutorials during the lockdown have contributed to body image issues. Emerging evidence from India suggests that peer-conversations about appearance as negative body talk (fat talk) is particularly salient in contributing to body dissatisfaction and body-perception ideals, which are more prevalent in women. Even though there has been growing research in the psychosocial impact of COVID-19, its influence on body-image perceptions and consequent distress have been stigmatized and under-spoken areas. With this background, this article reviews research on the biopsychosocial factors that influence body dissatisfaction among women, particularly the role of media. It also highlights the development of body image concerns in India, one of the worst-hit countries during the pandemic, through liberalization, importing Western notions of body instrumentality, the demographic shift and resultant social changes. Finally, the psychosocial strategies for positive body-image ideas to prevent and mitigate the adverse effects of body dissatisfaction are discussed, particularly those that focus on cognitive behavioural techniques (CBT) from the perspectives of positive psychology, media literacy programs, and involvement of the media. Interventions and further research to address body dissatisfaction among women, especially in the post-COVID aftermath need to be a recognized as a public health goal.